Effects of Continuous Exposure to Ozone Gas and Electrolyzed Water on the Skin Hardness of Table and Wine Grape Varieties. Issue 1 (27th October 2015) - Laureano, J.; Giacosa, S.; Río Segade, S.; Torchio, F.; Cravero, F.; Gerbi, V.; Englezos, V.; Carboni, C.; Cocolin, L.; Rantsiou, K.; Faroni, L.R.D.; Rolle, L.
Abstract: The effects of continuous exposure to ozone gas (O3, 30 μL/L, 24 h) and immersion in electrolyzed water (EW, 400 mg/L free chlorine, 10 min) on skin hardness of Italia and Muscat Hamburg table grapes, and Merlot and Barbera wine grapes were investigated and compared with those of control treatments (air and deionized water). Skin hardness was instrumentally evaluated via measurements of skin break energy using a puncture test. For all cultivars and density classes, ozone treatment was more effective in increasing skin hardness than EW treatment, although the differences were not always significant. For the same treatment, skin hardening was independent of berry density, and the magnitude of this effect was cultivar‐dependent. This skin hardening might positively affect the postharvest life of table grapes. In wine grapes, increases in skin break energy values were related to higher yields and slow extraction kinetics of phenolic compounds during maceration. Practical Applications: The purpose and the originality of this work were to determine the real impact of continuous exposure to ozone gas and immersion in electrolyzed water on skin hardness in table grape and wine grape varieties. Differences in the treatment effect due to the grape maturity level were studied in berries sorted according to density. For all cultivars and density classes evaluated, ozone treatment was more effective for increasing skin hardness than electrolyzed water treatment although the differences were not always significant. Therefore, the use of ozone gas as alternative sanitizing agent could extend the postharvest life of table grapes and facilitate the extraction of phenolic compounds from wine grapes during maceration according to increased skin hardness.